The Effect of Peer Editing Technique Toward Writing Skill in Narrative Text of The First Year Students at SMAN 3 Rambah Hilir - -, Kurniati; Sukma, Dian; Kasyulita, Evi (Jurnal Ilmiah Mahasiswa FKIP Prodi Bahasa Inggris, 2015)
The purpose of the research was to know the effect of peer editing technique toward writing skill in narrative text of the first year students at SMAN 3 Rambah Hilir. The method in this research was experimental research, pre test and post test design. The participants of the study are 41students. The results of this research are there was significant effect in post test with using peer editing technique. (To) value was 5.679 and (Tt) value was 2.020. It showed that (To) was higher than (Tt). The research concludes that there was significant effect to the students of Xb.